Health behavior change and treatment adherence evidence-based guidelines for improving healthcare - Martin, Leslie R.; Haskard-Zolnierek, Kelly B., 1978-; DiMatteo, M. Robin (New York ; Oxford : Oxford University Press, 2010)
This title synthesizes the results from more than 50 years of empirical research, resulting in simple, powerful, and practical guidance for health professionals who want to know the most effective strategies for helping their clients to put long-term health-relevant behaviour changes into practice.
Description based on print version record.
Includes index.
Keywords: Patient compliance; Health behavior; Evidence-based medicine